Improve performance of the digital sinusoidal generator in FPGA by memory usage optimization - Aiman Zakwan Jidin; Irna Nadira Mahzan; A. Shamsul Rahimi A. Subki; Wan Haszerila Wan Hassan (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper presented the improvement in the performance of the digital sinusoidal signal generator, which was implemented in FPGA, by optimizing the usage of the available memory onboard. The sine wave was generated by using a Lookup Table method, where its pre-calculated values were stored in the onboard memory, and its frequency can be adjustable by changing the incremental step value of the memory address. In this proposed research, the memory stores only 25000 samples of the first quarter from a period of a sine wave and thus, the output signal accuracy was increased and the output frequency range was expanded, compared to the previous research. The proposed design was successfully developed and implemented in ALTERA Cyclone III DE0 FPGA Development Board, and its functionality was validated via functional simulation in Modelsim and also hardware experimental results observation in SignalTap II.